Influência do processamento industrial nos compostos bioativos e voláteis de polpa de manga (Mangifera indica L.) - Silva, Elizabete de Santana (2018)
Mango (Mangifera indica L.) is a tropical fruit with a sweet taste and pleasant aroma. It can be found in the market in fresh form, or processed in the form of pulp, juices, sweets, and as an ingredient in several products. An important issue to be considered is that processing may end up modifying sensory and functional characteristics, a factor that influences consumer acceptance of the product. Therefore, the objective of this work was to evaluate the possible modifications resulting from the industrial processing of mango pulp of the "Maria" variety, volatile compounds, sensory profile, bioactive compounds and antioxidant activity of industrialized and in natura pulps. Firstly, the physical and chemical characteristics of the samples were evaluated through acidity, water activity, ash, color, lipid, pH, protein, soluble solids and moisture, according to the analytical standards of the Adolfo Lutz Institute. The bioactive compounds (phenolics and total flavonoids, total carotenoids, beta - carotene and ascorbic acid) and antioxidant activity, using the ABTS, DPPH, FRAP and ORAC techniques, were determined by means of spectrophotometric assays. The determination of the volatile profile was performed using the SPME (Solid Phase Micro Extraction) technique and its identification by gas chromatography coupled to a spectrometer, based on the NIST parameters and the retention index confirmed by the scientific literature. All the results obtained were statistically analyzed. In all physical-chemical parameters evaluated, significant differences were found between the samples (p <0.05). Regarding the bioactive compounds, significant differences were also found in all the analyzed pulps. For the antioxidant activity there were significant differences related to the choice of the chosen method of determination. The determination of the volatile compounds showed a significant change in the concentrations of the volatile compounds present in the in natura sample and in the processed samples. Thus, according to the results obtained, it can be concluded that industrial processing influences significantly the functional and sensory properties of industrialized mango pulp.